2017
DOI: 10.1007/s40610-017-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Retinal Stem Cell Therapy

Abstract: Purpose of review Progress in stem cell research for blinding diseases over the past decade is now being applied to patients with retinal degenerative diseases and soon perhaps, glaucoma. However, the field still has much to learn about the conversion of stem cells into various retinal cell types, and the potential delivery methods that will be required to optimize the clinical efficacy of stem cells delivered into the eye. Recent findings Recent groundbreaking human clinical trials have demonstrated both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 119 publications
(112 reference statements)
0
26
0
Order By: Relevance
“…MSCs are considered a promising cell type with high potential for a regenerative effect in various diseases [ 19 ]. ASCs have gained particular traction as a source of therapeutic MSCs due to their easy isolation from an abundant source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs are considered a promising cell type with high potential for a regenerative effect in various diseases [ 19 ]. ASCs have gained particular traction as a source of therapeutic MSCs due to their easy isolation from an abundant source.…”
Section: Discussionmentioning
confidence: 99%
“…A number of preclinical animal studies and clinical studies have attempted to develop therapeutic strategies or to halt the progression of TBI with no success to date [ 18 ]. Adult mesenchymal stem cells (MSCs) derived from the stromal vascular fraction of human adipose tissue (ASC, adipose stem/stromal cells) have therapeutic effects in a variety of neurovascular degenerative models [ 19 ]. However, poor cell retention and loss of cell viability and function in the hostile pro-inflammatory environment of injured tissue is a challenge for clinical adoption of cell-based regenerative therapies [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is an important message as clinical trials with stem‐cells (Bhattacharya et al. ; Takashima et al. ) and gene‐vectors (Ku & Pennesi ) have already been initiated in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances highlight the feasibility of cell-based therapies for the preservation and regeneration of the retinal neurovascular unit [ 23 ]. We have previously shown that intravitreal injection of adipose-derived stem cells (ASCs) in diabetic rats imparts neurovascular benefits [ 24 ] which were also confirmed by other independent investigators [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%